Prime Minister's Decree No. 2437 of the Year 202I issuing The Executive Regulations Of The Law on Social Insurance and Pensions As Promulgated by Law No. 148 of the Year 2019 2021 = قرار رئيس مجلس الوزراء رقم 2437 لسنة 2021 بإصدار اللائحة التنفيذية لقانون التأمينات الاجتماعية الصادر بالقانون رقم 148 لسنة 2019 قانون التأمينات الاجتماعية. - Egypt (2025)
Definition and insurance cover -- -- Chapter 2 Insurance coverage Social Insurance file -- Chapter4 Contribution procedures of Managing and financing the social insurance and prisons scheme Rules of establishing and managing the account of the insurance scheme Par-21 -- Chapter2 Rules, procedures and system of work of the committee of experts -- Chapter -- Chapter 4 Financial statements of the national organization for social Actuarial valuation of the social insurance counts -- Chapter 5 Managing the investment fund of social insurance moneys 32 Rules of determining and collecting contributions and calculation or contribution procedures for certain period -- Chapter I Contributory wage and income and contribution percentages Procedures of payment and delivery of the contributions Paying the due amounts in instalments Follow up procedures regaling payment of installments due on the parties concerned Calculation or contribution procedures concerning certain periods -- Chapter 1 -- Chapter-5: IS Part-4: Rules of calculation of insurance rights concerning Insurance of old age, disability and death -- Chapter- Pensions and compensations -- Chapter 2 Additional rights -- Chapter Remuneration -- Chapter 4 Additional pension -- Chapter 5 Pension increases Part-5: -- Chapter 1 -- Chapter 2 Provisions of the work Injury insurance Beneficiaries of the provisions of work injury in e Pender of importing injury and documents of the Injury file Promulge of establishing -- Conditions and procedures of the periodic medical examination for workers prone to occupational discases Procedures of treatment and medical care Rules and procedures pertaining to payment of wage compensation -- 5 Chapter 6 68 92 Chaper-7 Pension and the lump-sum compensation in work injury insurance Ueda upload par L6 -- Chapter-9 Chupter-10 Medical arbitration Medical re-examination – medical arbitrations -- Unemployment insurance provisions -- Chapter- 1 Categories benefiting from the provisions of the unemployment insurance and the conditions of entitlement to the compensation -- Chapter-2 Procedures of applying for the disbursement of the unemployment compensation 901 Workers' comp insurance LOI -- Chapter- 1: Insurance of contracting, building and construction workers, stevedores, and quarries and saline workers Insurance on fishing workers LOI 117 -- Chapter-2: -- Chapter 3: Roads transport workers insurance -- Chapter 4: Insurance on workers of traditional bread bakeries Part-R: -- Chapter- 1: Conditions of entitlement to pension and rules of pension 128 Persons entitled to pension distribution -- Chapter-2 Discontinuation of pension and disbursing marriage grant or discontinuation grant -- Chapter-3: Entitlement to pension on a date later than the date of the death of the insured or the pensioner Part-9 Documents and provisions of paying off insurance rights 1- Part -11: General and miscellaneous provisions Part-12: Traditional provisions